The Effect of Animated Video on Students’ Vocabulary Mastery at the Eighth-Grade of SMPN 3 Kramatwatu - Wulandari, Ratih Ayu; Fajruri (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2024)
This study aims to determine the effect of using animated videos on vocabulary mastery of class VIII students of SMPN 3 Kramatwatu. This study used a quasi-experimental research method with a nonequivalent control group design. The population in this study were all eighth-grade students at SMPN 3 Kramatwatu totaling 255 students, with two classes as samples, namely class 8A, consisting of 30 students, as the experimental class, and class 8B, consisting of 32 students, as the control class. The data collection technique involved the use of test consisting of 20 multiple-choice questions. For pretest hypothesis testing, a t-test was used, and the results showed a value of tcount = 2.043 and ttable = 2.009, indicating that there was difference between the experimental and control classes. For posttest hypothesis testing, the t-test results showed a value of tcount = 4.972 and ttable = 2.009 which indicated a significant difference between the experimental and control classes after the teaching-learning process. This shows that the use of animated video has a significant effect towards the vocabulary mastery of class VIII students of SMPN 3 Kramatwatu.